The critical role of TRIM protein family in intervertebral disc degeneration: mechanistic insights and therapeutic perspectives - Shangze Li; Wenli Jiang; Fei Chen; Jiao Qian; Jun Yang (Frontiers in Cell and Developmental Biology)
Intervertebral disc degeneration (IVDD) is a leading cause of chronic back pain, contributing significantly to reduced quality of life and global public health burdens. The TRIM (Tripartite Motif-containing) protein family, with its diverse regulatory roles, has emerged as a key player in critical cellular processes such as inflammation, cell death, and extracellular matrix (ECM) metabolism. Recent findings underscore the involvement of TRIM proteins in IVDD pathogenesis, where they regulate stress responses, maintain cellular homeostasis, and influence the functional integrity of nucleus pulposus (NP) and annulus fibrosus (AF) cells. This review explores the multifaceted roles of TRIM proteins in IVDD, highlighting their contributions to pathological pathways and their potential as therapeutic targets. Advancing our understanding of TRIM protein-mediated mechanisms may pave the way for innovative and precise therapeutic strategies to combat IVDD.